2012
DOI: 10.4028/www.scientific.net/ssp.187.57
|View full text |Cite
|
Sign up to set email alerts
|

A Hybrid Dry-Wet Approach for Removal of a Dummy Polysilicon Gate in a Replacement Metal Gate Scheme

Abstract: Beginning at the 45nm node, the semiconductor industry is moving to high-k gate dielectrics and metal gate electrodes for CMOS logic devices [. Although different approaches of building these devices are being pursued, most of the industry has consolidated behind a gate last approach, in which the transistor is built around a dummy poly polysilicon gate, which is subsequently removed and replaced with a metal gate. Current approaches to removing the dummy poly gate include plasma-based dry processes and liquid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Fig 3 is the result of partial etch performance on one commercial ICP etcher. [11] It is demonstrated that high current leakage occurred at longer dry etch process time. In 85S and 100S cases, polysilicon was completely removed by dry etching.…”
Section: Partition Etch Profile Comparisonmentioning
confidence: 96%
See 2 more Smart Citations
“…Fig 3 is the result of partial etch performance on one commercial ICP etcher. [11] It is demonstrated that high current leakage occurred at longer dry etch process time. In 85S and 100S cases, polysilicon was completely removed by dry etching.…”
Section: Partition Etch Profile Comparisonmentioning
confidence: 96%
“…However, this approach requires more complex process engineering at 3D structure. Both perfect physical structure and good electronic performance are challenging for dummy poly gate removal process [1][2][3][4][5][6]. As is well known, both dry etching and wet etching can effectively remove polysilicon.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation